SYSTEMATIC LITERATURE REVIEW TENTANG EFEKTIVITAS MODEL DISCOVERY LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN IPAS DI SEKOLAH DASAR - Dini Anggraeni; Dudu Suhandi Saputra; Dede Salim Nahdi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking is one of the essential 21st-century skills that should be developed through the learning process, particularly in Integrated Science and Social Studies (IPAS) learning at the elementary school level. One instructional model considered effective in fostering this skill is Discovery Learning. This study aims to examine the effectiveness of the Discovery Learning model in enhancing elementary school students’ critical thinking skills in IPAS learning through a Systematic Literature Review (SLR) approach. The study employed the SLR method following the PRISMA 2020 guidelines. Literature was collected from Google Scholar and Scopus databases using the Publish or Perish application, covering publications from 2019 to 2026. Through the processes of identification, screening, eligibility assessment, and inclusion, a total of 15 articles met the established criteria and were selected for analysis. The findings revealed that the quasi-experimental design was the most frequently used research method, while science education was the most commonly investigated subject area. Furthermore, all analyzed studies reported that the Discovery Learning model had a positive impact on students’ critical thinking skills. Its effectiveness was reflected in improvements in students’ ability to analyze information, solve problems, draw conclusions, and actively participate in the learning process. These findings indicate that Discovery Learning is an effective instructional model for enhancing elementary school students’ critical thinking skills in both science and IPAS learning, as it provides opportunities for learners to independently construct knowledge through observation, exploration, and inquiry activities.